The role of Yupa inscription as Yantra in Shiva worship: interpreting stone relics through contemporary practices in Kutai Kartanegara - I. Gusti Bagus Wirawan; I. Ketut Suda; I. Gede Adnyana; I. Wayan Sukadana; I. Nyoman Winyana; I. Made Yudabakti (Cogent Arts & Humanities, 2025)
Yupa or Lesong batu is a historical relic in Kutai Kartanegara that the community uses to honor King Mulawarman.The study aimed to reveal Yupa’s role as Yantra for ancestral and Shiva worship, historically and in the contemporary context. The use of Yupa as Yantra was influenced by historical, theological, cultural, and psychological factors. Through ethnographic investigation, we show how Yupa’s material presence mediates between cognitive religious concepts and ritual performances, establishing continuity between ancient texts and lived experiences. The process of Shiva worship using Yupa Yantra tended to align with the concept of Shiva Pitara. This worship process was rooted in the notions of creation (utpetti), preservation (stiti), and dissolution (pralina) of the universe. The stone relic encompassed diverse implications and meanings. These included theological aspects of Brahmanism-Shaivism, Shaktism, ancestor worship, Yoga Panca Korsika, Yupa as the center of ancestors, and the amplification of religious sentiments. This spiritual-material interface generates a psychological framework manifesting in collective social behaviors, creating community structures around the sacred object. Other implications included inter-tribal communication, religious harmony, religious tourism, cultural customs ‘ngugu lesung batu’ and ‘cerau’, and enhancement of Pamarangan cultural observer activities.